Measurement and Evaluation of Social Resilience Indicators in the Historical Neighborhoods of Tabriz City (Case Study: Sorkhab Neighborhood of Tabriz) - Leila Rahimi; Mahta Choobineh (برنامه ریزی فضایی)
AbstractGiven the significant social disruptions caused by natural disasters in urban areas fostering social resilience as a capability not only helps to maintain the initial performance of cities, but also contributes to their post-disaster improvement and prosperity. This study focused on evaluating the indicators of social resilience in the historical neighborhood of Sorkhab in Tabriz as these historical areas were among the most vulnerable parts of the city and played a crucial role in restoring normal social conditions. The research adopted a descriptive-analytical approach in terms of its nature and methodology. In the analysis section, SPSS software was utilized, employing one-way variance and sample t-test methods to examine the impacts of gender, age, and education on the three functional, social, and cultural dimensions. Furthermore, the most influential indicators were investigated using multivariate regression analysis. The research findings highlighted that the indicators of creating an inclusive urban space for all segments of society, fostering a sense of belonging and hope for the future of the neighborhood, were the most influential factors in promoting social resilience. Moreover, enhancing resilience in the face of crises necessitated increasing social interactions and raising people's awareness. Therefore, establishing a platform that fostered social interactions within the neighborhood and served as a hub for activities could expedite the neighborhood's recovery process during times of crisis.Keywords: Resilience, Social Resilience, Historical Context, Sorkhab Neighborhood of Tabriz IntroductionGiven the rapid population growth in cities, it is crucial to prioritize the social and administrative processes associated with urban functioning and evaluate residents' resilience to natural hazards (Hook et al., 2020: 98). Cities should be designed in a manner that minimizes risks, builds resilience, and enables swift recovery from disasters (Burton, 2015). Natural disasters have profound social repercussions in cities, making it imperative to promote social resilience as a capability that not only maintains cities' initial performance, but also fosters their post-disaster improvement and prosperity (Brown et al., 2012: 24). Resilient cities possess the ability to respond effectively to risks and stresses (Maguire et al., 2007: 16). However, in most studies on urban resilience, there is a relatively limited focus on assessing social and economic resilience compared to infrastructure, environmental, and institutional resilience (Sharifi, 2020). Social resilience aims to enhance the capacity to adapt to change, effectively navigate unexpected circumstances, and emphasize the significance of social relationships and individuals' sense of belonging to their living environment. Considering the vulnerability of historical neighborhoods, which are of significant importance, restoration of these areas to their desired living conditions is heavily influenced by their social status. Due to their age and lack of maintenance, historical neighborhoods often suffer from a diminished sense of belonging among residents. Additionally, these neighborhoods tend to attract individuals with limited financial means, who promptly relocate to better circumstances, indicating a lack of identity. The lack of social cohesion in such neighborhoods contributes to their limited resilience in the social dimension, necessitating a redesign that enhances neighborhood identity, social cohesion, and solidarity. The historical neighborhood of Sorkhab in Tabriz is one of the oldest neighborhoods in the city. However, this neighborhood has faced challenges related to deteriorating identity and neglected social relations. During natural disasters or other man-made issues, the social damages observed at the neighborhood level and dissatisfaction of residents with social conditions are indicative of the neighborhood's inability to adapt to changes. This is primarily due to the insufficient solidarity, sense of belonging, and participation among residents, which are essential social assets for fostering resistance and resilience against sudden changes. Consequently, the current conditions have failed to meet the residents’ social needs. Therefore, the aim of this research was to explore the components of social resilience in the historical context of Sorkhab Neighborhood in Tabriz. By utilizing the findings and results of this study, urban design projects could be informed to enhance the quality of urban spaces and promote social resilience. Materials and MethodsThis research adopted a descriptive-analytical approach in terms of its nature and methodology. The required information and data were gathered through a comprehensive review of relevant literature using library sources. The extracted indicators and criteria were then analyzed. Some criteria did not necessitate a questionnaire or collection of people's opinions. Therefore, the analysis and interpretation of these indicators and criteria in Sorkhab Neighborhood were conducted through field sampling and observation methods. However, certain criteria required a questionnaire and inclusion of people's opinions. To collect the opinions of individuals residing in the historical context of Sorkhab Neighborhood regarding social resilience, a survey was administered in the form of a questionnaire. The questionnaire was designed using a Likert scale. To assess the impact of gender, age, and education on the functional, social, and cultural dimensions (excluding the physical dimension, which did not require a questionnaire), one-way variance tests and t-tests were employed. Furthermore, the most influential indicators were examined using multivariate regression analysis. Based on the questionnaire results and tests, solutions were proposed to enhance social resilience. The compiled questionnaire evaluated the dimensions and components identified in the previous sections from the perspective of the citizens. It included individual questions concerning age, gender, education, as well as questions related to functional, cultural, and social aspects, which were assessed using a 5-point Likert scale ranging from "very low" to "very high". SPSS software was utilized to perform one-way variance tests and one-sample t-tests, enabling the investigation of the effects of gender, age, and education on the three dimensions. The sampling method employed was completely random with residents of the neighborhood being surveyed. Sorkhab Neighborhood had a population of 1204 individuals and 384 households. Based on Cochran's test, with an error rate of 0.063, 200 questionnaires were completed. The highest frequency of respondents was male accounting for 61%, while the lowest frequency was female at 44%. Research FindingsThe overall findings of the analysis revealed that, with the exception of criteria, such as access to services, a sense of belonging, and unity among residents, the neighborhood did not exhibit favorable conditions across the remaining criteria. These results emphasized the importance of enhancing residents' awareness in both functional and social dimensions with age being a significant influencing factor in the social dimension. Therefore, when setting goals for these dimensions, it was crucial to consider the preferences and tastes of each generation. The factor of gender played a notable role in the cultural dimension, highlighting the need for establishing fairness between the two gender groups.Among all the criteria, the sense of belonging and hope for the neighborhood's future had the greatest impact on increasing social resilience. On the other hand, the criterion of creating social groups to address neighborhood issues demonstrated the least influence. Among the various dimensions, the cultural dimension exerted the most significant impact on social resilience, demanding greater attention compared to the other dimensions. In terms of the physical aspect, it was evident that Sorkhab Neighborhood lacked designated spaces for residents. The limited number of activities within the neighborhood could be attributed to the presence of abandoned spaces predominantly used as parking lots, which failed to attract people and consequently have a low level of utilization. The aging buildings in the neighborhood, due to its historical nature, rendered many of them uninhabitable. Furthermore, the narrow width of local roads compromised the safety of both residents and users within the neighborhood. Overall, the physical condition of the neighborhood was unsatisfactory, posing significant challenges for residents and creating hazardous conditions during crises and even in normal circumstances. Discussion of Results and ConclusionIn this study, the scholars’ opinions were examined and the indicators of social resilience were extracted and investigated in the historical neighborhood of Sorkhab, Tabriz. The findings indicated that the functional dimension was influenced by the factor of education, while the social dimension was influenced by both age and education. The cultural dimension emerged as the most influential dimension with age and gender exerting an impact on this dimension. Among the indicators, creating an inclusive urban space, fostering a sense of belonging, and instilling hope for the neighborhood's future were found to be the most influential factors contributing to social resilience.The results highlighted the importance of increasing social interactions and raising awareness to enhance resilience in the face of crises. By improving educational and informational opportunities for all residents of the neighborhood and creating safe spaces that facilitate social interaction and presence, it is possible to directly improve social resilience and foster a stronger sense of membership and pride. The sense of belonging and hope for the future of the neighborhood are particularly impactful. Therefore, establishing a platform that promotes social interactions and serves as a hub for neighborhood activities would lead to a swift restoration of the neighborhood during times of crisis. Additionally, providing necessary psychological support training to influential individuals within the neighborhood during crises can be effective in encouraging and reassuring residents.